Amplification of WHSC1L1 regulates expression and estrogen‐independent activation of ERα in SUM‐44 breast cancer cells and is associated with ERα over‐expression in breast cancer. Issue 6 (27th February 2016) - Irish, Jonathan C.; Mills, Jamie N.; Turner-Ivey, Brittany; Wilson, Robert C.; Guest, Stephen T.; Rutkovsky, Alexandria; Dombkowski, Alan; Kappler, Christiana S.; Hardiman, Gary; Ethier, Stephen P.
Abstract : The 8p11‐p12 amplicon occurs in approximately 15% of breast cancers in aggressive luminal B‐type tumors. Previously, we identified WHSC1L1 as a driving oncogene from this region. Here, we demonstrate that over‐expression of WHSC1L1 is linked to over‐expression of ERα in SUM‐44 breast cancer cells and in primary human breast cancers. Knock‐down of WHSC1L1, particularly WHSC1L1‐short, had a dramatic effect on ESR1 mRNA and ERα protein levels. SUM‐44 cells do not require exogenous estrogen for growth in vitro; however, they are dependent on ERα expression, as ESR1 knock‐down or exposure to the selective estrogen receptor degrader fulvestrant resulted in growth inhibition. ChIP‐Seq experiments utilizing ERα antibodies demonstrated extensive ERα binding to chromatin in SUM‐44 cells under estrogen‐free conditions. ERα bound to ERE and FOXA1 motifs under estrogen‐free conditions and regulated expression of estrogen‐responsive genes. Short‐term treatment with estradiol enhanced binding of ERα to chromatin and influenced expression of many of the same genes to which ERα was bound under estrogen‐free conditions. Finally, knock‐down of WHSC1L1 in SUM‐44 cells resulted in loss of ERα binding to chromatin under estrogen‐free conditions, which was restored upon exposure to estradiol. These results indicate the SUM‐44 cells are a good model of a subset of luminal B breast cancers that have the 8p11‐p12 amplicon, over‐express WHSC1L1, and over‐express ERα, but are independent of estrogen for binding to chromatin and regulation of gene expression. Breast cancers such as these, that are dependent on ERα activity but independent of estradiol, are a major cause of breast cancer mortality. Highlights: SUM44 is a model cell line for ERα positive breast cancer with the 8p11 amplicon. WHSC1L1 is a driving oncogene from the 8p11 amplicon in SUM44 cells. SUM44 breast cancer cells have high ERα expression, regulated by WHSC1L1 knockdown. ERα is required for growth and survival of SUM44 cells but is estrogen‐independent. WHSC1L1 knock‐down re‐sensitizes ERα to estradiol for binding to essential genes.